The Image Of The Father In The Work Of Nabi Jalalidin (Texas Journal of Philology, Culture and History, 2025)
The article examines the work of Nabi Jaloliddin, one of the most talented representatives of 21st-century Uzbek prose, and his mastery of creating an image in the story "Father". The responsibility, human qualities, and changes in the spirit of the father in the story are analyzed